Respuesta :

Answer:

x = - 8

Step-by-step explanation:

Given

6(x - 1) = 9(x + 2) ← distribute parenthesis on both sides

6x - 6 = 9x + 18 ( subtract 9x from both sides )

- 3x - 6 = 18 ( add 6 to both sides )

- 3x = 24 ( divide both sides by - 3 )

x = - 8

The value of x in the equation given which is 6(x – 1) = 9(x + 2) is D. x = 8

The equation given is:

6(x – 1) = 9(x + 2)

In order to solve for x, we've to remove the parentheses. This will be:

6(x – 1) = 9(x + 2)

6x - 6 = 9x + 18

Add 6 to both side

6x= 9x + 18 + 6

6x = 9x + 24

Collect like terms

9x - 6x= 24

3x = 24

x = 24/3

x = 8

In conclusion, the value of x is 8.

Read related link on:

https://brainly.com/question/13448236

ACCESS MORE